Optimum Solution of Resource Leveling Problem by Evaluating the Whole Search Domain - Bettemir, Önder Halis; Erzurum, Tuğba (Fırat University, 2022)
The endeavor to minimize the fluctuations of the resource assignments without postponing the project deadline is named as resource leveling problem. This problem is solved by heuristic methods, consist of simple rules, meta-heuristic methods, explore the search domain systematically but randomly, and analytical methods. Nevertheless, aforementioned approaches come to be insufficient when the number of activity of the project increases which oversize the search domain of the resource leveling problem. In this study, the number of the feasible solutions is determined by detecting the number of feasible schedules obtained by delaying the noncritical activities without violating the restrictions on the activities. The entire search domain is evaluated and the optimum feasible solution is obtained in a guaranteed manner. Suitability of the resource distribution is evaluated by minimum moment metric. A spreadsheet application is developed and macro is written by Visual Basic programming language to implement the developed method. In the literature survey, twenty seven resource leveling problems are collected and optimum solutions of them are obtained by the developed method. Definition of the parameters and the evaluation of the search domain of the resource leveling problem by the spreadsheet application are explained in detail on two of the solved case study problems so that the researchers can implement the developed method. Moreover the developed method is coded on C++ in order to expedite the computations. Test problems are also solved by genetic algorithm and the computation duration and the obtained results are compared with the proposed method. The comparison reveals that the developed method can be implemented for optimizing the resource distribution. Moreover, this research contributes to the literature by providing a methodology for the determination of the search domain of the resource leveling problem.

İnşaat süresi boyunca kaynak kullanımında gözlemlenen dalgalanmaların proje süresinde gecikme olmadan asgari düzeye indirilmesi kaynak dengeleme problemi olarak tanımlanır. Bu problem basit kurallar içeren sezgisel, sistematik fakat rassal biçimde arama uzayını tarayan üst-sezgisel ve analitik yöntemlerle çözülmektedir. Ancak aktivite sayısının artması ile arama uzayı çok büyüyen kaynak dengeleme probleminin çözümünde oluşan sorunlara karşı belirtilen yöntemler yetersiz kalmaktadır. Bu çalışmada, aktiviteler arasındaki kısıtlar ihlal edilmeden kritik olmayan aktivitelerin ertelenmesi ile kaç farklı şekilde uygulanabilir çözüm elde edilebileceği hesaplanarak kaynak dengeleme probleminin arama uzayının büyüklüğü belirlenmiştir. Belirlenen arama uzayının tamamı taranarak uygulanabilir en iyi çözüm garantili biçimde elde edilmiştir. Kaynak dağılımının uygunluğu minimum moment ölçeği ile incelenmiştir. Yöntemin uygulanabilmesi için bir hesap tablosu uygulaması oluşturularak Visual Basic programlama dilinde makro yazılmıştır. Literatürden derlenen 27 kaynak dengeleme probleminin geliştirilen yöntemle optimum çözümü elde edilmiştir. Hesap cetveline kaynak dengeleme probleminin nasıl tanıtılacağı çözülen problemler arasından seçilen 2 örnek problem üzerinde detaylı biçimde anlatılarak yöntemin tüm araştırmacılar tarafından uygulanabilmesi sağlanmıştır. Ayrıca geliştirilen yöntem çözüm süresini kısaltmak için C++ dilinde de kodlanmıştır. Test problemleri genetik algoritmayla çözülmüş, hesaplama süreleri ve sunduğu sonuçlar önerilen yöntemin çıktıları ile karşılaştırılmıştır. Çözüm süresi ve çözüm iyiliğinin karşılaştırılması sonucunda geliştirilen yöntemin kaynak dengeleme probleminin kesin çözümünde uygulanabilir olduğu belirlenmiştir. Ayrıca çalışma kaynak dengeleme probleminin arama uzayını belirleyen bir yöntem geliştirerek literatüre katkı sağlamaktadır.
Tüm Arama Uzayı Taranarak Kaynak Dengeleme Probleminin Optimum Çözülmesi
Keywords: Engineering; Mühendislik